Disgrasya sa kadalanan, atong likayan a communication campaign to promote safety awareness and responsibilities among motorcycle drivers - Ocho, Orlaine Rexie Mae (2019)
As motorcycles have been known to be the most convenient form of transportation in the Philippines, accidents involving them have been common incidents in the country as well. Motorcycles have been recorded as especially poor in safety as compared to other vehicles. To avoid these accidents, it is important for the motorcycle drivers to be aware of the safety precautions as well as the traffic rules and regulations that they should abide to. Although the same rules and regulations regarding motorcycle vehicles are being implemented by all LTO branches all over the country, information dissemination strategy including necessary information on the road safety and road user?s responsibilities is at the discretion of each branch. Since there is no uniform communication strategy used to disseminate necessary information that is being utilized by all the LTO branches, each branch is entitled to develop their own strategy on how to properly disseminate information towards their constituent motorcycle drivers. LTO-Kidapawan branch lacks a communication strategy which makes it difficult for them to disseminate necessary information to their consistent motorcycle drivers. Thus, the development of the campaign entitled, ?Disgrasya sa Kadalanan, Atong Likayan?. The researcher utilized the rope process in order to develop the campaign. The research component gathered data from the LTO through a key informant interview and from the respondents from Barangay Kisante, the locale of the study, through a survey. Documents from the aforementioned barangay and the implementing organization were obtained and studied to assess the effectivity of the campaign/s they implemented before.